Factors that influenced the purchase of gemstone among enthusiast in Kelantan - Marzuki, Ibrahim; Mohd Zamani, Daud; Nur Syafinaz, Mohd Anuar (2021)
This research has been conducted to identify three main factors i) the level of knowledge on gemstone, ii) the choices of the types of gemstone among enthusiast, iii) factors that influenced the purchase of gemstone. A quantitative research questions were used to collect information and answered the aforementioned main factors. The total of 302 respondents includes Malay male from all over Kelantan. The focus of the research is on the knowledge of gemstone only in the category of precious gemstone which are diamond, ruby, sapphire and emerald. The outcome of the analysis shows over 86.1% of respondent can identify the characteristics of natural or synthetic gemstone. However, over 66.6% of respondents are not confident with the naturalness of the purchased gemstone and are not familiar with the term of the treated gemstone and gemstone certificate. The knowledge about gemstone colour, gemstone-producing countries and the price of gemstone are from the range of 17% to 84%. Ruby was the most popular choice among the respondents and the price that respondents willing to pay for a gemstone are between RM 500 - RM 1000. Moreover, most of the respondents agreed that personal factors (age, profession, economy, life style, personality) influenced individual in purchasing the gemstone. Overall, it can be included that the level of knowledge of gemstone among enthusiast in Kelantan is at alarming level based on the findings that 76.8% of the enthusiast are not familiar with the terms of treated gemstone and gemstone certificate.